2016
DOI: 10.1111/trf.13535
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial damage‐associated molecular patterns as potential proinflammatory mediators in post–platelet transfusion adverse effects

Abstract: PLT-derived mitochondrial DAMPs are candidate risk factors for the onset of NHTRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 56 publications
1
45
1
Order By: Relevance
“…Our own group has reported that there is a direct relationship between (i) the secretion of sCD40L [proved to exert a pathogenic effect in certain recipients, together with companion BRMs Ox40L and IL-27 (64, 65)] and the component shelf life; and (ii) between the net amount of sCD40L (alongside potentiating molecules IL-13 or MIP-1α) and the manifestation of an inflammatory AE in the recipient (62). Similar findings exist for mitochondrial DNA (6668). In addition, it has also been proposed that the techniques used to obtain PCs influence pro-inflammatory reactions, as these techniques do not expose platelets to the same stress (62, 69).…”
Section: Models Of Transfusion-associated Inflammation Hitsupporting
confidence: 81%
“…Our own group has reported that there is a direct relationship between (i) the secretion of sCD40L [proved to exert a pathogenic effect in certain recipients, together with companion BRMs Ox40L and IL-27 (64, 65)] and the component shelf life; and (ii) between the net amount of sCD40L (alongside potentiating molecules IL-13 or MIP-1α) and the manifestation of an inflammatory AE in the recipient (62). Similar findings exist for mitochondrial DNA (6668). In addition, it has also been proposed that the techniques used to obtain PCs influence pro-inflammatory reactions, as these techniques do not expose platelets to the same stress (62, 69).…”
Section: Models Of Transfusion-associated Inflammation Hitsupporting
confidence: 81%
“…mtDNA is a highly potent inflammatory mediator when present extracellularly 26,43 and may cause transfusion-related side effects. 44 We observed that the level of extracellular mtDNA did not significantly increase in apheresis PCs upon the RF/UV treatment and during storage. Recently, Cognasse and coworkers 45 reported that extracellular mtDNA is consistently increased in PCs from Day 1 to Day 4 but decreased on Day 5 of storage.…”
mentioning
confidence: 67%
“…We previously reported that the BAT was used as a functional test in transfusion medicine to assess the causal relationship between ATRs and the transfusion and to examine whether the reactions occurred through an allergen/IgE‐dependent or allergen/IgE‐independent pathway . Moreover, both pathways of basophil activation can be assessed by the BAT . However, those studies had several limitations.…”
Section: Discussionmentioning
confidence: 99%